(untitled) - Aretha Brito Nobre; Juan Piñeiro-Maceira; Ronir Raggio Luiz (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Dysplastic nevi are among the most important cutaneous melanoma simulators. They are important risk markers for this neoplasia and can be its potential precursors. Some authors found a statistically significant relationship between the degree of dysplasia and the risk for developing melanoma. However, reproducibility of grading criteria ranged from poor to fair in the researched articles. OBJECTIVE: To test the reproducibility of the grading criteria proposed by Sagebiel et al. regarding dysplastic nevi. METHODS: Histological specimens of 75 dysplastic nevi were graded, independently and in a blinded fashion, according to preestablished criteria, by a panel of 10 pathologists with different levels of experience. Diagnostic agreement was calculated using weighted kappa and intraclass correlation coefficients. RESULTS: The average of weighted kappa values was 0.13 for all observers, 0.12 for dermatopathologists, 0.18 for general pathologists and 0.05 for residents. Intraclass correlation coefficient values were 0.2 for all observers, 0.18 for dermatopathologists, 0.33 for general pathologists and 0.15 for residents. CONCLUSIONS: Histopathological grading for dysplastic nevi was not reproducible in this Brazilian series, so the criteria used are not a helpful histopathological parameter for clinicopathological correlation. FUNDAMENTOS: Nevos displásicos estão entre os mais importantes simuladores de melanoma. São marcadores de risco para o desenvolvimento dessa neoplasia e podem ser seus precursores. Alguns autores observaram uma relação estatisticamente significativa entre o grau de displasia e o risco de desenvolvimento de melanoma. No entanto, a reprodutibilidade dos critérios para graduação variou de ruim a razoável nos artigos consultados. OBJETIVO: Testar a reprodutibilidade da graduação proposta por Sagebiel et al. para os nevos displásicos. MÉTODOS: Seções histológicas de setenta e cinco nevos displásicos foram graduadas, de forma independente e anônima, segundo critérios pré-estabelecidos, por um painel de 10 patologistas com diferentes níveis de experiência. A concordância diagnóstica foi calculada usando os coeficientes de kappa ponderado e de correlação intraclasse. RESULTADOS: A média dos valores de kappa ponderado foi de 0,13 para todos os observadores, de 0,12 para os dermatopatologistas, de 0,18 para os patologistas gerais e de 0,05 para os residentes. Os valores dos coeficientes de correlação intraclasse foram 0,2 para todos os observadores, 0,18 para os dermatopatologistas, 0,33 para os patologistas gerais e 0,15 para os residentes. CONCLUSÕES: A graduação histopatológica dos nevos displásicos não foi reprodutível nesta série brasileira. Portanto, os critérios utilizados não são úteis para correlação clínico-patológica.